Psychopharmacological treatment differences in autogenous and reactive obsessions: A retrospective chart review. (2nd January 2016) - Batmaz, Sedat; Yildiz, Mesut; Songur, Emrah
Abstract : Background: Identification of homogeneous subgroups of obsessive compulsive disorder (OCD) patients may have important implications for improving effective treatment options. It has been proposed that obsessive thoughts can be classified into two subtypes, i.e. autogenous and reactive obsessions. Although it has been shown that patients with autogenous obsessions may display a worse response to treatment, no studies have yet addressed whether there is a different need for the psychopharmacological treatment options in the subtypes of OCD patients. Aim: To investigate the clinical characteristics and treatment differences between autogenous (A-OCD) and reactive (R-OCD) subtypes of OCD patients. Methods: Both OCD subgroups ( n = 50 for A-OCD, n = 130 for R-OCD) were compared with each other in terms of their demographic and clinical parameters. Odds ratio values for gender, treatment options, co-morbidity, severity of OCD, and response to treatment were computed. Multivariate hierarchical regression analyses were performed to identify any predictors for treatment options, severity of OCD, and response to treatment. Results: Our results indicated that the A-OCD and R-OCD groups differed from each other on some demographic and clinical variables in addition to their psychopharmacological treatment needs. Patients in the A-OCD group were found to be prescribed an atypical antipsychotic 2.3 times more likely than the R-OCD group. The odds for a combination treatment, or the improvement of OCD symptoms from baseline levels did not differ between the two subtypes of obsession groups. Conclusions: Autogenous and reactive subtypes of obsessions may need to be offered different psychopharmacological treatment options.